Eliminating Plastic Pollution: How a Voluntary Contribution From Industry Will Drive the Circular Plastics Economy - Forrest, Andrew; Giacovazzi, Luca; Dunlop, Sarah; Reisser, Julia; Tickler, David; Jamieson, Alan; Meeuwig, Jessica J. (Frontiers in Marine Science, 2019)
Marine plastic pollution is a symptom of an inherently wasteful linear plastic economy, costing us more than US$ 2.2 trillion per year. Of the 6.3 billion tonnes of fossil fuel-derived plastic (FFP) waste produced to date, only 9% has been recycled; the rest being incinerated (12%) or dumped into the environment (79%). FFPs take centuries to degrade, meaning five billion tonnes of increasingly fragmented and dangerous plastics have accumulated in our oceans, soil and air. Rates of FFP production and waste are growing rapidly, driven by increased demand and shifting strategies of oil and gas companies responding to slowing profit growth. Without effective recycling, the harm caused by FFP waste will keep increasing, jeopardizing first marine life and ultimately humankind. In this Perspective article, we review the global costs of plastic pollution and explain why solving this is imperative for humanity’s well-being. We show that FFP pollution is far beyond a marine environmental issue: it now invades our bodies, causing disease and dysfunction, while millions of adults and children work in conditions akin to slavery, picking through our waste. We argue that an integrated economic and technical solution, catalyzed through a voluntary industry-led contribution from new FFP production, is central to arrest plastic waste flows by making used plastic a cashable commodity, incentivizing recovery and accelerating industrialization of polymer-to-polymer technologies. Without much-needed systematic transformation, driven by a contribution from FFP production, humanity and the oceans face a troubling future.